PENERAPAN TERAPI KOMBINASI BUTTERFLY HUG DAN NATURE SOUND TERHADAP SKOR KECEMASAN PADA LANSIA DI PANTI WERDHA WELAS ASIH KABUPATEN TASIKMALAYA: APPLICATION OF BUTTERFLY HUG AND NATURE SOUND COMBINATION THERAPY ON ANXIETY SCORES IN THE ELDERLY AT THE WELAS ASIH NURSING HOME IN TASIKMALAYA - Sopia Siti Rohmah Sunarya; Iwan Somantri; Ridwan Kustiawan; Asep Riyana (Quality: Jurnal Kesehatan, 2026)
Anxiety is a psychological problem commonly experienced by the elderly, especially those living in nursing homes due to environmental changes, limited activities, and reduced social support. Untreated anxiety can negatively affect physical health, psychological well-being, and quality of life. Therefore, safe, simple, and easy-to-apply non-pharmacological interventions are needed, such as a combination therapy of butterfly hug and nature sound. This study aimed to determine the effect of the combination therapy of butterfly hug and nature sound on anxiety scores among the elderly. The study was conducted on December 16–22, 2025, at Welas Asih Nursing Home, Tasikmalaya Regency. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 38 elderly participants selected using the total sampling technique. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS). Data analysis used the Paired t-test to determine differences in anxiety scores before and after the intervention. The results showed that the average anxiety score before the intervention was 25.63 and decreased to 18.53 after the combination therapy of butterfly hug and nature sound was administered. Statistical analysis showed a p-value < 0.000 (p < 0.05), indicating a significant effect of the combination therapy on reducing anxiety scores among the elderly. This therapy can be recommended as a non-pharmacological intervention to improve psychological well-being and quality of life among elderly individuals in nursing homes.